Penulisan Butir Soal Berbasis Higher Order Thinking Skills (HOTS) - Munali Munali; Shinta Dewi; Siti Alifah; Sri Hapsari (Universitas Muhammadiyah Mataram, 2026)
Abstract: Partner problems currently faced by teachers at SMKN 54 Jakarta: 1) lack of teacher ability in writing test items with revised Bloom's Taxonomy, especially based on HOTS, 2) lack of teacher ability in writing test items for the Academic Ability Test (TKA), and 3) lack of teacher ability in scoring analytical rubrics on essay test items and TKA test items. Partner problems are mainly related to the results of SMKN TKA in Jakarta, with a national average of 38.25 in the fields of study: Mathematics at 38.25; English at 31.29; and Advanced Mathematics at 39.61. The objectives of Community Service (PkM) activities: 1) provide teachers' understanding of writing test items with revised Bloom's Taxonomy, especially based on HOTS, 2) improve teachers' ability in writing test items for TKA, and 3) improve teachers' ability in scoring analytical rubrics on essay test items and TKA test items. The research methodology uses a qualitative approach through observation, interviews, and discussions. Activities are carried out through the following stages: pre-activity, activity implementation, and monitoring and evaluation. The pre-activity phase includes coordination with partners, needs analysis, preparation of presentation materials, and event rundown. The implementation phase lasts two days. The monitoring and evaluation phase is conducted after the workshop through observation, discussion, and Q&A. The results of the Community Service Program (PKM) show that the activity's objectives were achieved well in both soft and hard skill aspects. This can be seen from the measurements.Workshop on the first and second days. Measurements from the first and second days of the workshops showed a 25% increase in teachers' ability to understand HOTS test writing, TKA, and analytical rubric scoring. This increase demonstrates the effectiveness of the workshop support on the first and second days.Abstrak: Permasalahan mitra yang sedang dihadapi oleh guru di SMKN 54 Jakarta: 1) kurangnya kemampuan guru dalam penulisan butir soal dengan Taksonomi Bloom revisi terutama berbasis HOTS, 2) kurangnya kemampuan guru dalam penulisan butir soal Tes Kemampuan Akademik (TKA), dan 3) kurangnya kemampuan guru dalam penskoran rubrik analitik pada butir soal esai dan butir soal TKA. Permasalahan mitra terutama terkait hasil TKA SMKN di Jakarta dengan rerata nasional bidang studi: Matematika sebesar 38,25; Bahasa Inggris sebesar 31,29; dan Matematika Lanjut sebesar 39,61. Tujuan kegiatan Pengabdian kepada Masyarakat (PkM): 1) memberikan pemahaman guru dalam penulisan butir soal dengan Taksonomi Bloom revisi terutama berbasis HOTS, 2) meningkatkan kemampuan guru dalam penulisan butir soal TKA, dan 3) meningkatkan kemampuan guru dalam penskoran rubrik analitik pada butir soal esai dan butir soal TKA. Metodologi penelitian menggunakan pendekatan kualitatif melalui: observasi, wawancara, dan diskusi. Kegiatan dilaksanakan melalui tahapan: prakegiatan, pelaksanaan kegiatan, dan monitoring dan evaluasi. Pada tahap prakegiatan dilakukan koordinasi dengan mitra, analisis kebutuhan, persiapan materi presentasi, dan rundown acara. Tahap pelaksanaan dilakukan selama dua hari. Tahap monitoring dan evaluasi dilakukan setelah kegiatan workshop melalui observasi, yaitu diskusi dan tanya jawab. Hasil PkM menunjukkan bahwa tujuan kegiatan tercapai dengan baik pada aspek soft skill dan hard skill. Hal ini terlihat dari pengukuran workshop hari pertama dan hari kedua. Pengukuran workshop hari pertama dan hari kedua menunjukkan peningkatan kemampuan guru dalam memahami penulisan butir soal HOTS, TKA, dan penskoran rubrik analitik sebesar 25%. Peningkatan tersebut menunjukkan efektivitas pendampingan workshop pada hari pertama dan hari kedua.